Mechanism of hypocoagulability in proton-irradiated ferrets - Krigsfeld, Gabriel S. (2013)
PURPOSE: To determine the mechanism of proton radiation-induced coagulopathy. MATERIAL AND METHODS: Ferrets were exposed to either solar particle event (SPE)-like proton radiation at a predetermined dose rate of 0.5 Gray (Gy) per hour (h) for a total dose of 0 or 1 Gy. Blood was collected pre- and post-irradiation for a complete blood cell count or a soluble fibrin concentration analysis, to determine whether coagulation activation had occurred. Tissue was stained with an anti-fibrinogen antibody to confirm the presence of fibrin in blood vessels. RESULTS: SPE-like proton radiation exposure resulted in coagulation cascade activation, as determined by increased soluble fibrin concentration in blood from 0.7 – 2.4 at 3 h, and 9.9 soluble fibrin units (p < 0.05) at 24 h post-irradiation and fibrin clots in blood vessels of livers, lungs and kidneys from irradiated ferrets. In combination with this increase in fibrin clots, ferrets had increased prothrombin time and partial thromboplastin time values post-irradiation, which are representative of the extrinsic/intrinsic coagulation pathways. Platelet counts remained at pre-irradiation values over the course of 7 days, indicating that the observed effects were not platelet-related, but instead likely to be due to radiation-induced effects on secondary hemostasis. White blood cell (WBC) counts were reduced in a statistically significant manner from 24 h through the course of the seven-day experiment. CONCLUSIONS: SPE-like proton radiation results in significant decreases in all WBC counts as well as activates secondary hemostasis; together, these data suggest severe risks to astronaut health from exposure to SPE radiation.